Pretreatment and enzymatic hydrolysis optimization of lignocellulosic biomass for ethanol, xylitol, and phenylacetylcarbinol co-production using Candida magnoliae - Porninta, Kritsadaporn; Khemacheewakul, Julaluk; Techapun, Charin; Phimolsiripol, Yuthana; Jantanasakulwong, Kittisak; Sommanee, Sumeth; Mahakuntha, Chatchadaporn; Feng, Juan; Htike, Su Lwin; Moukamnerd, Churairat; Zhuang, Xinshu; Wang, Wen; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Cellulosic bioethanol production generally has a higher operating cost due to relatively expensive pretreatment strategies and low efficiency of enzymatic hydrolysis. The production of other high-value chemicals such as xylitol and phenylacetylcarbinol (PAC) is, thus, necessary to offset the cost and promote economic viability. The optimal conditions of diluted sulfuric acid pretreatment under boiling water at 95°C and subsequent enzymatic hydrolysis steps for sugarcane bagasse (SCB), rice straw (RS), and corn cob (CC) were optimized using the response surface methodology via a central composite design to simplify the process on the large-scale production. The optimal pretreatment conditions (diluted sulfuric acid concentration (% w/v), treatment time (min)) for SCB (3.36, 113), RS (3.77, 109), and CC (3.89, 112) and the optimal enzymatic hydrolysis conditions (pretreated solid concentration (% w/v), hydrolysis time (h)) for SCB (12.1, 93), RS (10.9, 61), and CC (12.0, 90) were achieved. CC xylose-rich and CC glucose-rich hydrolysates obtained from the respective optimal condition of pretreatment and enzymatic hydrolysis steps were used for xylitol and ethanol production. The statistically significant highest (p ≤ 0.05) xylitol and ethanol yields were 65% ± 1% and 86% ± 2% using Candida magnoliae TISTR 5664. C. magnoliae could statistically significantly degrade (p ≤ 0.05) the inhibitors previously formed during the pretreatment step, including up to 97% w/w hydroxymethylfurfural, 76% w/w furfural, and completely degraded acetic acid during the xylitol production. This study was the first report using the mixed whole cells harvested from xylitol and ethanol production as a biocatalyst in PAC biotransformation under a two-phase emulsion system (vegetable oil/1 M phosphate (Pi) buffer). PAC concentration could be improved by 2-fold compared to a single-phase emulsion system using only 1 M Pi buffer.